Suporte para Transmissão de Mídia entre Servidor e Clientes Cooperativos - Shimoda, Marcio Akio; Trevelin, Luis Carlos (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2005: Anais do VI Workshop em Sistemas Computacionais de Alto Desempenho, 2005)
In this research we address the problem of the distribution of multimedia content for a large number of computers. Specifically, we consider the problem of the overload of the server, that occurs due to the fast increase of the volume of solicitations to receive content. We present as solution a communication model to complement the traditional client-server. It is based on the cooperative networks, in which the customers cooperares to distribute the media, where they act as a kind of temporary server, until the server come back to the normal one.